Management of paclitaxel-induced neurotoxicity - Manisha Bhutani; Philomena M. Colucci; Heather Laird-Fick; Barbara A. Conley (Frontiers Media S.A., 2011)
Paclitaxel exerts its antitumor activity by promoting microtubule assembly and stabilizing microtubules. Microtubules are important for the development and maintenance of neurons. As a consequence, neurotoxicity is one of the drug's major side effects. The risk of neurotoxicity depends on dose, duration and schedule of paclitaxel. Risk increases for patients with pre-existing conditions that may cause neuropathy (such as alcohol consumption, diabetes, or renal disease) or with simultaneous or prior exposure to other neurotoxic chemotherapy such as platinum-based drugs, vinca alkaloids, immunomodulators, proteasome inhibitors, and epothilones. Patients with paclitaxel-induced neurotoxicity (PINT) experience a constellation of symptoms over the course of treatment and beyond, ranging from mild to severe. Typically, the clinical presentation reflects an axonal peripheral neuropathy with glove-and-stocking distribution sensory loss, combined with features suggestive of nerve hyperexcitability including paresthesia, dysesthesia, and pain. Proprioceptive and motor effects become apparent as neuropathy becomes more advanced. These symptoms may be prolonged, severe, disabling, relatively resistant to intervention and adversely affect activities of daily living and thereby quality of life. Management is mainly symptomatic and supportive. Despite attempts to minimize PINT with changes in dose, vehicle, delivery systems, infusion schedule and premedication or co-treatment with neuroprotective agents, PINT remains dose-limiting in many instances and is a barrier to achieving the desired clinical response.